HUBUNGAN KONSEP DIRI DAN HARGA DIRI PADA PERILAKU ASERTIF REMAJA KELAS XI SMA ANTARTIKA SIDOARJO - Utomo, Anggitha Listyo (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research aims to determine the relationship between self-concept and assertive behavior in class XI students at Antarctica Sidoarjo High School. This research uses quantitative correlational research methods. The population in this study amounted to 504 classes. The self-concept data collection technique uses a self-concept scale, for self-esteem data uses a self-esteem scale, while for data on assertive behavior uses an assertive behavior scale. The research data analysis technique uses multiple correlation analysis. The results of Pearson correlation analysis show that there is a significant positive relationship between self-concept and assertive behavior, r=0.263, (p-value kecil dari .001) and between self-esteem and assertive behavior (r=0.333, p-value kecil dari .001). So it can be concluded that there is a unidirectional relationship between self-concept and self-esteem and assertive behavior, where the higher the level of self-concept and self-esteem of the research sample, the higher the level of assertive behavior they have research sample.